Subject and partner satisfaction with lip and perioral enhancement using flexible hyaluronic acid fillers - Bertucci, Vince; Nikolis, Andreas; Solish, Nowell; Lane, Vanessa; Hicks, Jessica (Journal of cosmetic dermatology, 2021)
Background The injection of hyaluronic acid (HA) dermal fillers is a popular minimally invasive approach to improve lip volume and contour, and with improved techniques has gained popularity because full lips are often associated with beauty and youth. Patient satisfaction is a key driver for successful aesthetic procedures, influencing individual treatment plans and future recommendations. Objective To evaluate subject and partner satisfaction with the hyaluronic acid (HA) dermal filler HARK for lip enhancement at 8 weeks after the last treatment. Methods & materials Subjects in this open‐label study all received HARK in the lips, and an additional group also received HARR and/or HARD in nasolabial folds (NLFs) and marionette lines (MLs). Satisfaction was assessed at Weeks 4 and 8 after the last treatment using questionnaires (FACE‐Q™ [subjects] and KISSABILITY [subjects and partners]). Results Nineteen subjects received HARK only; 40 also received HARR and/or HARD. Subjects reported a high level of satisfaction with their lips following treatment. Increases from baseline in the mean total satisfaction score were statistically significant at Weeks 4 and 8 (P ≤ .001). Most subjects (≥89%) reported satisfaction on all FACE‐Q questions at Week 8. Both subjects and partners were satisfied with the kissability, appearance, and natural look and feel of the post‐treatment results. Conclusion This study demonstrated that HARK resulted in lip enhancement with high levels of subject and partner satisfaction, when used alone or in combination with HARR/ HARD in NLFs and MLs.